Development of oil-in-water emulsions based on rice bran oil and soybean meal as the basis of food products able to be included in ketogenic diets - Benitez, Lucas Osvaldo (2020)
The aim of this work was to develop rice bran oil-in-water emulsions stabilized with proteins and polysaccharides from soybean meal as the basis of food products able to be included in ketogenic diet. The effect of the formulation (ketogenic ratios and oil mass fractions) and the high-pressure homogenization conditions (number of homogenization cycles) on the properties of the resulting O/W emulsions was evaluated. All freshly prepared emulsions showed multimodal particle size distributions and shear-thinning behaviour. At a fixed ketogenic ratio, all emulsions had the same oil to emulsifiers + stabilizers proportion, but increasing their oil mass fraction resulted in systems composed by smaller particles with greater interfacial area, and apparent viscosity. The same effect was observed by increasing the number of homogenization cycles. Meanwhile, increasing the ketogenic ratio (at a fixed oil mass fraction) diminished its apparent viscosity. Most of the studied emulsions were stable for seven days of quiescent refrigerated storage, although some changes in its particle size distributions were observed. Only, the stored emulsions with the highest ketogenic ratio and the lowest oil mass fraction presented gravitational separation but no phase separation. Emulsions prepared after five homogenization cycles presented greater stability to the coalescence than those prepared in one cycle.